‘Living in Sick Europe is Spiritually More Interesting than in Healthy and Well-fed America’: A.V. Kartashev’s Letters to E.I. Novitskii, 1948–1951 - Aleksandr V. Antoshchenko (Historia provinciae: журнал региональной истории, 2020)
This publication includes letters from Anton V. Kartashev, a renowned historian, a professor at St. Sergius Orthodox Theological Institute (Institut de théologie orthodoxe Saint-Serge) in Paris, sent to his friend Evgenii I. Novitskii, who had moved from France to the USA not long before. In the introduction, the publisher describes the context, in which the letters were written, which makes it possible to better understand their meaning and value as a historical source. The letters characterize Anton Kartashev’s attitude of towards the idea of reuniting Russian Orthodox parishes in emigration, which were under the jurisdiction of different church organizations. The historian considered it possible to unite them under the seniority of Metropolitan Anastasii (Gribanovskii) and under the jurisdiction of the Patriarchate of Constantinople but doubted the fulfilment of this possibility due to the accumulated canonical contradictions. Particular attention is paid to the relations between the Russian Exarchate in Western Europe and the Russian Orthodox Greek Catholic Church in the United States, as well as the possibility of educating graduates of St. Tikhon’s Theological Seminary (Pennsylvania) at the institute. In addition to the information about the persons and events mentioned in the correspondence, the commentary includes fragments from letters of the historian’s wife, Pavla P. Kartasheva, which reveal the nuances of what was sometimes only briefly reported by her husband. Among the latter there are the demarcation between the generations of “fathers” and “sons” at the institute, which led to the departure of young professors to America, and the trip of the Kartashevs to Italy.